Parental attachment, smartphone addiction and stress among undergraduate students - Tan, Pey Shyan; Arshat, Zarinah (Global Academic Excellence, 2019)
This study aims to determine the relationships between parental attachment, smartphone addiction and stress among undergraduate students. By using a multi-stage cluster random sampling technique, a total of 400 respondents were involved in this study. Inventory of Parent and Peer Attachment-Revised Mother, Father and Peer Attachment version was used to measuring parental attachment. Smartphone Addiction Scale-Short Version was used to measure smartphone addiction and Perceived Stress Scale-10 was used to measure stress. As expected, mother attachment, father attachment, and smartphone addiction were significantly correlated with stress. Meanwhile, there were no significant differences in smartphone addiction and stress between male and female undergraduate students. This study concluded that parental attachment and smartphone addiction were significant in influencing the stress level of undergraduate students. By understanding the impact of parental attachment and smartphone addiction towards stress among undergraduate students, it helped to enhance the understanding of sources of stress in order to promote effective stress management.